Defect-induced Ce3+ sites preferences and multilevel concentration quenching of a high-efficiency cyan phosphor for high-quality full-visible-spectrum wLED. Issue 39 (14th September 2022) - Piao, Siqi; Wang, Yichao; Wang, Chuang; Zhou, Xufeng; Zhang, Jinsu; Zhang, Xizhen; Cao, Yongze; Chen, Baojiu
Abstract : The emission light of CSBO: Ce 3+ changes from blue to broad band cyan emission with the increase of Ce 3+ concentration resulted from defect-induced site selective occupation. The full-spectrum emission WLED of 93.2 color rendering index was obtained. Abstract : Currently, the efficient way to synthesize white light-emitting diodes (WLEDs) is combining a near-ultraviolet (n-UV, 380–420 nm) emitting LED chip with tricolor (red, green, and blue) emitting phosphors. However, further improving the color rendering index (CRI) for WLEDs is hindered by the absence of cyan components. Hence, a series of high-efficiency and continuously tunable Ce 3+, Gd 3+ -doped CaScBO4 (CSBO) blue–cyan phosphors with an orthorhombic structure were successfully developed by a high-temperature solid-state reaction method. Based on density-functional theory (DFT) calculation, a vacancy was produced along with inequivalent replacement (3Ca 2+ → 2Ce 3+ /Gd 3+ + V′′Ca ) when just adding the trivalent cations, meanwhile causing the local environment of the lattice to relax so Ce 3+ /Gd 3+ ions find it easier to enter into Sc 3+ sites at a higher doping concentration. Under the excitation of n-UV, the emission peak position moves from 443 nm to 480 nm and two concentration quenching points appear with an increase in Ce 3+ ions by defect-induced site-selective occupation. The two samples at concentration quenching points both have high quantum efficiencies of 88.6% and 86.2% and an acceptable thermal quenching performance. The property performance and internal mechanism are illuminated by the excitation and emission spectra and theoretical analysis. Finally, by combining CSBO:Ce 3+, commercial green and red phosphors and an n-UV LED chip, an as-fabricated WLED with a great CRI value of 93.2 and a low CCT (4291K) was obtained. This work demonstrates the potential of CSBO:Ce 3+ as a blue–cyan phosphor for use in high-quality full-visible-spectrum WLEDs in the future. The investigation of the mechanism for the defect-induced site preferences provides a reference for developing new photoluminescent materials.